1987
DOI: 10.1128/jb.169.10.4731-4736.1987
|View full text |Cite
|
Sign up to set email alerts
|

Transverse membrane topography of the B875 light-harvesting polypeptides of wild-type Rhodobacter sphaeroides

Abstract: Purified B875 light-harvesting complex, chromatophores, and spheroplast-derived vesicles from wild-type Rhodobacter sphaeroides were treated with proteinase K or trypsin, and the a and ,B polypeptides were analyzed by electrophoretic, immunochemical, and protein-sequencing methods. With the purified complex, proteinase K digested both polypeptides and completely eliminated the A875 peak. Trypsin digested the a polypeptide and reduced the A875 by 50%. Proteinase K cleaved the , polypeptide of chromatophores and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…-ATPase. It is well established that the F 1 part of ATPase is localized on the outer surface of chromatophore (Oelze 1978;Takemoto and Bachmann 1979), whereas the C-terminal portions of all the LH polypeptides are orientated to the internal space of the chromatophores Takemoto et al 1987;Tadros et al 1988). Under the condition of this study, EDTA was essentially unable to penetrate into the membrane vesicles, but the membrane can be easily solubilized by the detergents.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…-ATPase. It is well established that the F 1 part of ATPase is localized on the outer surface of chromatophore (Oelze 1978;Takemoto and Bachmann 1979), whereas the C-terminal portions of all the LH polypeptides are orientated to the internal space of the chromatophores Takemoto et al 1987;Tadros et al 1988). Under the condition of this study, EDTA was essentially unable to penetrate into the membrane vesicles, but the membrane can be easily solubilized by the detergents.…”
Section: Discussionmentioning
confidence: 82%
“…It has been well established that the chromatophore has an inside-out orientation where the cytoplasmic inner surface of intracytoplasmic membrane is exposed to the external medium (Oelze and Drews 1972;Matsuura and Nishimura 1977;Lommen and Takemoto 1978;Oelze 1978;Takemoto and Bachmann 1979). The methods used for identifying the orientation of chromatophore have also been applied to determine the membrane topology of LH and RC polypeptides Takemoto et al 1987;Tadros et al 1988;Pugh et al 1998). It is shown that the N-termini of all LH polypeptides, including PufX, are exposed to the cytoplasmic surface of membrane, while the C-termini are exposed to the periplasmic membrane surfaces.…”
Section: Introductionmentioning
confidence: 98%
“…Although at present little is known about the assembly pathway of the LH1 complex, topology studies have demonstrated that the C-terminal regions of both the ␣ and the ␤ polypeptides are located on the periplasmic side of the membrane (25). Thus it is conceivable that truncations of the C terminus of the ␣ polypeptide would affect the process by which it is translocated across the bilayer, leading to a decrease in the level of the ␣ polypeptide in the membrane, accompanied by a decrease in the stability of the ␤ polypeptide.…”
Section: Discussionmentioning
confidence: 99%
“…The polypeptides of the core LHC of these three bacteria have been sequenced and are similar in hydrophobicity and molecular weight (Brunisholz and Zuber, 1988;Zuber, 1986). These polypeptides are membrane-spanning with their N-termini near the cytoplasmic surface and their C-termini near the periplasmic surface (Brunisholz et al, 1984;Tadros et al, 1986a, b;Takemoto et al, 1987). Reconstitution results strongly suggest that BChl binding in "B820" complexes is primarily to the p polypeptides and Rs.…”
Section: Comparison Of Subunits From Rs Rubrum Rb Sphaeroides Andmentioning
confidence: 99%